Identifying research priorities for improving patient care in the perioperative environment: A descriptive cross-sectional study - Nicholson, Patricia; Hamlin, Lois; Duff, Jed; Gillespie, Brigid; Williams, Carollyn (Operating Room Nurses Association of Canada Journal, 2024)
Changes in the delivery of patient care, the rapid evolution of technology and the complexity of the current health care environment require health professionals to make clinical decisions that are both current and evidence-based.1,2 Perioperative nursing has a long history steeped in tradition and routine practice and although evidence-based practice (EBP) has existed for decades, a number of barriers to implementing this practice in the operating room have been identified.3,4 Perioperative nurses are accountable for the care provided to patients presenting for surgery; therefore, implementation of EBP is important for standardising patient care1 and supporting positive patient outcomes. By incorporating EBP skills in perioperative nursing, a rationale for current practices in the operating suite is also justified.1 With increased accountability for the quality of care provided in the perioperative environment, the value of perioperative nurses’ contribution to patient care has been questioned.5 In order to increase the quality and efficiency of patient care, perioperative nurses’ contribution to research and research utilisation in the perioperative environment is crucial6. It is important to identify priority, relevant research questions to address the gap that exists between data that is generated by researchers and the information that is required by end-users.7 Despite the importance of this, there is limited evidence about how research priorities should be established.8 This study was undertaken to identify research priorities in perioperative nursing and identify areas of practice that could inform the development of new standards of practice for perioperative nurses.